El futuro y el tiempo histórico en la filosofía de la historia de Hegel - Belvedresi, Rosa (Revista Eletrônica Estudos Hegelianos, 2016)
In this paper we analyze the role that the future plays in the Hegelian philosophy of history. Mind requires time to reach a mediate consciousness of itself, since it gains its reality through the process of the universal history. There is an evolution in history because Mind is the absolute possibility. But Mind is always present so it seems that no future is needed for its development. The future can be understood as a dimension of the historical time or as a logical condition derived from the teleological structure of Mind. In the latter, the future appears as a non-historical time because in the universal history only what is needed happens, that is, the fulfillment of the ideal. What we will try to show is that the very Hegelian model of history requires the future as historical time in order to grasp the political nature of Mind as State.